Diagnosis of NUT carcinoma of lung origin by next-generation sequencing: case report and review of the literature. Issue 2 (1st February 2019) - Mao, Naiquan; Liao, Zhiling; Wu, Junwei; Liang, Kai; Wang, Shoufeng; Qin, Shaomian; Dou, Ying; Lin, Hanqing; Dong, Xiaowei
ABSTRACT: NUT carcinoma (NC) is an aggressive squamous tumor characterized by NUT gene rearrangement, and the most common fusion form is BRD4-NUT . However, NC diagnosis is difficult for its rareness and often being confused with a variety of poorly differentiated tumors. A 21-year-old Chinese woman was referred to our hospital for cough and intermittent fever. Chest computed tomography (CT) imaging revealed a left lobe hilar mass. Fiberoptic bronchoscopy results showed that tumor cells were poorly differentiated. In combination with immunohistochemistry staining, she was misdiagnosed with Ewing's sarcoma/primitive neuroectodermal tumor. Next-generation sequencing (NGS) revealing BRD4-NUT fusion, and NUT immunohistochemistry confirmed the diagnosis of NC. Subsequently, left pneumonectomy and lymph node dissection were performed, and the patient received pemetrexed and lobaplatin treatment. NGS technology played an important role in NC diagnosis in this case, and it may have clinical use for rare cancer diagnosis and guidance of potential targeted therapies.